An Open Markov Model for Determination of Urban Area size Distribution with Applications to Data on Urbanisation in Nepal - Shrestha, H. B. (Himalayan Review, 2011)
Not avialable. Key words: Open markov; Urban area; Nepal The Himalayan Review Vol. XVI, 1985 Page: 1-6 Uploaded Date: 19 April, 2011